Motivation for MOOC learning persistence: An expectancy–value theory perspective - Lee, Yechan; Song, Hae-Deok (Frontiers in Psychology, 2022)
Managing learning continuity is critical for successful MOOC learning. Thus, enabling learners to have learning persistence needs to be integrated in the MOOC learning design. Motivation effort is a critical component enabling students to maintain continuous MOOCs learning. Expectancy-value theory explains why learners engage in learning: they have higher perceived ability for learning success, place value on learning, and avoid psychological cost. However, it is unclear how these factors affect MOOC learning persistence and how learners’ motivation is formed from this perspective. This experimental study explored how learners' motivational variables affect their learning persistence, focusing on the expectancy-value theory. The results of this study indicated that academic self-efficacy and task value had significant positive effects on learning persistence. The structural relationship of antecedent, process, and outcome variables showed that teaching presence as an antecedent had a significantly positive effect on academic self-efficacy and task value. Among the three factors of the expectancy-value theory, only the task value influenced learning persistence through student engagement as a mediator. Based on the results, suggestions are provided for motivating MOOC environments that support learners’ continuous MOOC learning.